2006
DOI: 10.1097/01.jcp.0000237950.65517.be
|View full text |Cite
|
Sign up to set email alerts
|

Manic/Hypomanic Switch During Acute Antidepressant Treatment for Unipolar Depression

Abstract: A significant proportion of patients with unipolar depression clinically develop manic or hypomanic switch during acute antidepressant treatment. Elucidation of its prevalence and predicting factors is of clinical relevance during acute antidepressant treatment of such patients. We retrospectively studied patients with unipolar depression who were admitted to our department during the 6-year period from 1997 to 2002 and who had fewer than 3 previous episodes before admission. The clinical background of the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 16 publications
3
23
0
Order By: Relevance
“…In prospective studies, all who developed antidepressant-associated mania went on to later have episodes of spontaneous mania though these studies included a limited number of cases with pharmacologically-induced hypomania (10, 14). The family histories of those with antidepressant-associated mania further resemble those of individuals with spontaneous mania For these reasons, opinion leaders do not currently distinguish antidepressant-induced manias from those that arise spontaneously (38) and this assumption underlies our analyses (39, 40). The proposed revisions for DSM-V now also include the caveat “A full manic or hypomanic episode emerging during antidepressant treatment (medication, ECT etc) and persisting beyond the physiological effect of that treatment is sufficient evidence for a manic or a hypomanic episode diagnosis.”…”
Section: Discussionmentioning
confidence: 99%
“…In prospective studies, all who developed antidepressant-associated mania went on to later have episodes of spontaneous mania though these studies included a limited number of cases with pharmacologically-induced hypomania (10, 14). The family histories of those with antidepressant-associated mania further resemble those of individuals with spontaneous mania For these reasons, opinion leaders do not currently distinguish antidepressant-induced manias from those that arise spontaneously (38) and this assumption underlies our analyses (39, 40). The proposed revisions for DSM-V now also include the caveat “A full manic or hypomanic episode emerging during antidepressant treatment (medication, ECT etc) and persisting beyond the physiological effect of that treatment is sufficient evidence for a manic or a hypomanic episode diagnosis.”…”
Section: Discussionmentioning
confidence: 99%
“…Faedda and colleagues 32 reported that AEMS was more frequent in girls, but Wada and colleagues 30 reported that the proportion of men was significantly higher in the AEMS group than in the non-AEMS group. Faedda and colleagues 32 reported that AEMS was more frequent in girls, but Wada and colleagues 30 reported that the proportion of men was significantly higher in the AEMS group than in the non-AEMS group.…”
Section: Discussionmentioning
confidence: 98%
“…AEMS was observed in 7% to 17% of youths with depression 8,29,30 and 50% to 58% of youths with BD. AEMS was observed in 7% to 17% of youths with depression 8,29,30 and 50% to 58% of youths with BD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Manic or hypomanic switches were most frequently observed between 2 and 3 weeks after the antidepressant dose was increased. 10 Cases of mania have been reported under escitalopram therapy in patients with no history of mania. 11,12 In the present case, because the patient had taken escitalopram for 6 months, the risk for a switch to mania was decreased but remained still possible, particularly in the absence of a mood stabilizer.…”
Section: Discussionmentioning
confidence: 99%